Social Services for the Community: Leveraging Buddhist Religious Resources in Ho Chi Minh City, Vietnam - Lộc, Dương Hoàng (Journal of Ecohumanism, 2025)
Religious resources have become a significant topic of interest and discussion in Vietnam, particularly regarding their potential to enhance the role of religions in contributing to national development and the process of international integration. This study examines the role of Buddhism in delivering social services to the community in Ho Chi Minh City, Vietnam, by exploring its religious resources. The findings reveal that Buddhism in Ho Chi Minh City actively provides free educational and healthcare services to support the poor and urban migrants in overcoming hardships. These efforts highlight the religion's social function in promoting social justice in Vietnam. The study concludes that through its practical contributions to the community, Buddhism serves as a valuable religious resource in Vietnam, especially in Ho Chi Minh City. Based on these insights, the article proposes several solutions to enhance the role of Buddhism in offering social services to the community in Ho Chi Minh City, Vietnam.